Association between iron deficiency anemia and febrile seizures - Dr Kunwar Bharat; Dr Rajesh K. Yadav; Dr Durgesh Kumar; Dr Amitesh Yadav; Dr Rajiv Sharan; Dr Vineet Chaturvedi (Pediatric Review: International Journal of Pediatric Research, 2015)
Background: Febrile seizure is a common cause of seizure in young children, with an excellent prognosis. There is high prevalence of febrile seizure and iron deficiency anemia in preschool children, the aim of this study was to investigate the role of iron deficiency anemia in simple febrile seizure patients. Methods: This prospective case-control study was performed in 50 children with simple febrile seizures (cases) and 50 febrile children without seizures (control), referred to Tata Motors Hospital, Jamshedpur. All children were aged between 6 months-5year. The groups were matched in age, gender, height and weight. Laboratory investigations performed were complete blood count, serum electrolytes, liver function test and renal functions test. Specific test advised were hemoglobin (Hb), (MCH), Mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), and plasma ferritin (PF). Results: There is lower value of hematological indices like mean Hemoglobin, Mean corpuscular hemoglobin, Mean corpuscular volume, Mean corpuscular hemoglobin concentration and Serum Ferritin in the cases group compared to the control group but no statistically significant difference. Conclusion: This study did not establish any association between iron deficiency anemia and febrile seizures.